Tunable accordion optical lattice for precise control of Rydberg atom interactions in magneto-optical traps (MOTs) - Zhang, Hao; Miao, Ying; Cao, Yifei; Liang, Xue; Jing, Mingyong; Zhang, Linjie (Review of scientific instruments, 2025)
Precise control of Rydberg atom interactions in magneto-optical traps is essential for advanced quantum technologies, yet fine-tuning of strong Rydberg interactions remains challenging. To address this, we present a tunable accordion optical lattice with dynamically adjustable lattice spacings. By stabilizing power and polarization, we improve the power stability of the device by 56.53%, achieving lattice spacings ranging from 46.63 to 2.58 μm and generating stable interference patterns consistent with theoretical predictions. The lattice’s versatility and precision enable control of atomic interactions, supporting simulations of quantum phase transitions and many-body physics while advancing quantum simulations and information processing.